TANTANGAN DALAM PENGEMBANGAN UMKM DI TASIKMALAYA - Anggraini, Winda Ayu; Rosidah, Euis (Balance : Jurnal Akuntansi dan Bisnis, 2023)
This study analyzes the business challenges of small, micro, and medium enterprises in Tasikmalaya. This study uses a case study method using triangulation at Sale Pusaka which produces banana sale products. Sale Pusaka is located in Cibanteng Village, Tasikmalaya and has been producing banana sale since 1979. The results of the study explain that Sale Pusaka faces business challenges in the form of a limited financing structure, management of marketing strategies that are not optimal, preparation of financial reports that are not adequate and the availability of quality human resources which is lacking. The solution that researchers can submit in facing these challenges is to open up additional opportunities by applying for credit, updating the quality of resources and adding workers for the business’s continuity. In addition, researchers suggest that Sale Pusaka remain focused and diligent in managing their business consistently and sustainably by producing daily, routine promotions and evaluations.